The Effects of Sons and Daughters on Men's Labor Supply and Wages - Lundberg, Shelly; Rose, Elaina (The Review of Economics and Statistics, 2002)
In this paper, we estimate the effects of children and the differential effects of sons and daughters on men's labor supply and hourly wage rates. The responses to fatherhood of two cohorts of men from the PSID sample are examined separately, and we use fixed-effects estimation to control for unobserved heterogeneity. We find that fatherhood significantly increases the hourly wage rates and annual hours of work for men from both cohorts. Most notably, men's labor supply and wage rates increase more in response to the births of sons than to the births of daughters.